Crossopsorella, a new tropical genus of rust fungi - Souza, Erica S. C.; Aime, M. Catherine; Elias, Samuel G.; Pinho, Danilo B.; Miller, Robert. N. G.; Dianese, José C. (Phytotaxa, 2018)
Prior phylogenetic studies of rust fungi have shown the Phakopsoraceae as polyphyletic. However, most of the ca. 13 genera currently placed in Phakopsoraceae s.l. have not been the subject of phylogenetic analyses. In this study we examine the placement of several species of Crossopsora (Phakopsoraceae) from newly generated nuc 28S rDNA (28S) sequence data. While the type species, C. ziziphi, cannot be excluded from the Phakopsoraceae s.s., several other species, including C. byrsonimae, are not congeneric with the type. Herein we describe the new genus Crossopsorella, based on C. byrsonimae as the type, to accommodate specimens of this species found in four different Byrsonima species.